(untitled) (Communication & Society, 2020)
This article analyses the relations between citizens and the electoral campaign regarding insecurity/lack of public safety during the presidential election of 2015. Crime was one of the major concerns of the country that year, so much so that four of the six candidates produced specific election advertising spots on the subject. Within this context, the article asks: What does insecurity mean for citizens? Do they support the promises of the campaign? How do they interpret audio-visual materials about insecurity? The aim is to explore how those viewers interpreted campaign publicity on insecurity/crime during the presidential election of 2015 and to reflect on their role in the processes of political mediatization. Analyzing six focal groups, we were able to conclude that: i. People experience worry about crime in the city and distrust not only the police but the legal system and political representatives; ii. They do not criticize the candidates’ promises, but they can unveil the true or false intentions of election advertising; iii. They distinguish between election advertising aimed at an emotional response (false) and those more logical or rational (closer to the truth).